The Effect of Service Quality Moderated Policy Promotion on Customer Trust: A Study of the Port Sector - Rosita Septiani; Rahmi Fahmy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper aims to examine and build a conceptual model regarding the effect of the effectiveness of service quality on the level of customer trust in the port sector in Indonesia. This study explores the value and need to significantly increase competitiveness in the port industry by identifying empirically in improving service quality as well as looking for whether the promotion of policies carried out can affect customer trust. Research design, data and methodology based on online survey by distributing questionnaires with ship owners and ship management. In this study, samples were taken by accident as many as 100 representative ships accessing anchorage services in the waters of the Indonesian archipelago. The estimation results of the regression model show that there is a linear relationship between service quality, policy promotion and the interaction between the two and service quality on the object of this study has an impact on customer trust.